(untitled) (Current Horticulture, 2024)
The experiment was conducted to find out the interactive effect of organic manures and fertility levels on three-year-old ber (Zizyphus mauritiana Lamk.) plants of cv. Gola at SKN College of Agriculture, Jobner, Rajasthan (India), during 2015-2016. The experiment consisted of 20 treatment combinations with four levels of organic manures (M0, control, M1, FYM @ 20 kg/plant, M2, vermicompost @ 6 kg/plant and M3, poultry manure @ 8 kg/ plant) and five levels of RDF (F0, control, F1, 50% RDF, F2, 75% RDF, F3, 100% RDF and F4, 125% RDF) in a randomized block design with three replications. The results revealed that integration of organic manures and inorganic fertilizers was more effective in increasing growth and yield of ber plants than inorganic fertilizers alone. Among various combinations, application of vermicompost @ 6 kg/plant with 125% RDF (M2F4) proved the best treatment combination in terms of number of secondary branches per primary branch (10.39), fruit yield (18.54 kg/plant and 51.54 q/ha) and net returns (`1,53,869/ha), whereas vermicompost @ 6 kg/plant with 100% RDF (M2F3) proved best in respect to B:C ratio (2.96) as compared to other treatment combinations.